ANALISIS YURIDIS PENDAFTARAN FIDUSIA ONLINE OLEH NOTARIS MELALUI WEBSITE ADMINISTRASI HUKUM UMUM: ANALISIS YURIDIS PENDAFTARAN FIDUSIA ONLINE OLEH NOTARIS MELALUI WEBSITE ADMINISTRASI HUKUM UMUM - ACHMAD SAIFULLAH; MUHAMMAD ALI; KHUSNUL HITAMINAH (JUSTNESS - Jurnal Hukun dan Agama, 2025)
Abstract The registration of fiduciary collateral is mandatory . Article 13 of the Fiduciary Guarantee Law states that fiduciary registration is carried out by the fiduciary recipient, representative, or their attorney A notary as an attorney can also help the fiduciary recipient in registering the fiduciary deed at the fiduciary registration office.So the formulation of the problem in this journal is How is the procedure for online fiduciary registrationvia the AHU website by a notary and what is the responsibility of the notary in implementing data input for online fiduciary registration via the AHU website?. At present, fiduciary registration can be done online through the general legal adminstration website .Therefore, legal research is needed on Analysis Of Online Fiduciary Registration Process By Notaries Through General Legal Adminstration Website. This research adobts law nomatif reserarch and for further analyzed through legislative and conceptual approach using the method normative juridical Approach that utilizesl primary, secondary and tertiary legal sources to analyze various regulations in the field of notary law, the regulations regarding fiduciary registration by notaries, and books related to the fiduciary guarantees. Fiduciary Online must be carefully accepted by the notary, the notary's responsibility is greater, A thorough understanding of the registration procedures and requirements, readiness of complete and verified documents, careful utilization of the online system are key factors in the success of online fiduciary registration. The integrity of a notary is crucial to avoid violations of applicable rules and laws. Notarial deeds hold strong legal power, thus notaries must steer clear of dishonesty, manipulation, withholding of information, breaches of trust, fraud, or any legal violations linked to corporate crimes Keywords: Registration, Online fiduciary,Notary